Migrating foreign body granulomas after rupture of a breast implant - Teresa Grünke; Stephan Forchhammer; Anneli Vollert; Martin Schaller; Valentin Aebischer (Wiley, 2024)
Abstract We present the case of an 80‐year‐old female with a history of bluish streaks and painful lumps on her left arm, initially misdiagnosed as a soft tissue infection. Further investigation revealed granulomatous infiltrates in the arm and a ruptured breast implant. Upon presentation, nodular and painful swelling prompted a new biopsy. Histology and electron spectroscopy confirmed silicone deposits within granulomas. The rupture of the breast implant was identified as the likely source of silicone migration to the arm, possibly exacerbated by a past fall. Treatment challenges included the extensive size of the granuloma, leading to a trial of methotrexate therapy with initial improvement but subsequent discontinuation due to poor tolerance. This case underscores the potential for silicone migration from ruptured breast implants to induce distant granulomatous reactions, necessitating individualised treatment approaches.